1996
DOI: 10.17763/haer.66.2.n551658577h927h4
|View full text |Cite
|
Sign up to set email alerts
|

How We Find Ourselves: Identity Development and Two Spirit People

Abstract: Psychological theorists have typically treated sexual and racial identity as discrete and independent developmental pathways. While this simplifying division may make it easier to generate theory, it may also make it less likely that the resulting theory will describe people's real-life developmental experiences. In this article, Alex Wilson examines identity development from an Indigenous American perspective, grounded in the understanding that all aspects of identity (including sexuality, race and gender) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 1 publication
2
64
0
Order By: Relevance
“…There has been a broader consideration of the ways race and culture interact with the process of sexual identity development and the experience of non-heterosexuality in the United States (e.g., Boykin, 1996;Espin, 1993;Wilson, 1996). What it means to identify as same-gender loving is different across cultural contexts, and the process of identifying as a "dual minority" (sexual and racial or ethnic) calls on additional skills in code switching and environmental scanning.…”
Section: Lgbt Identity Developmentmentioning
confidence: 99%
“…There has been a broader consideration of the ways race and culture interact with the process of sexual identity development and the experience of non-heterosexuality in the United States (e.g., Boykin, 1996;Espin, 1993;Wilson, 1996). What it means to identify as same-gender loving is different across cultural contexts, and the process of identifying as a "dual minority" (sexual and racial or ethnic) calls on additional skills in code switching and environmental scanning.…”
Section: Lgbt Identity Developmentmentioning
confidence: 99%
“…Sioui (as cited in Wilson, 1996) has reported that on the North American continent there are more than 500 Nations, or tribes. Nonetheless, there are some commonalties that can inform the understanding of some of the factors that might contribute to the experiences of Native American lesbians.…”
Section: Lesblansmentioning
confidence: 99%
“…Nonetheless, there are some commonalties that can inform the understanding of some of the factors that might contribute to the experiences of Native American lesbians. One important influence is the centrality of spirituality and the strength of its ability to unite people (Tafoya, 1997; W. L. Williams, 1996;Wilson, 1996). There is a core belief that all that exists has a direct connection to the spirit world.…”
Section: Lesblansmentioning
confidence: 99%
See 2 more Smart Citations